Crafting a colorful home : a room-by-room guide to personalizing your space with color - Nicholas, Kristin (Roost Books, 2015)
Learn how to make your home sing through handmade crafts and a bold use of color. Kristin Nicholas, color expert and all-around master crafter, shares her secrets to selecting colors and patterns and explores the variety of crafts and decorating touches that have made her home so unique.